2013
DOI: 10.1271/bbb.130178
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Xanthurenic Acid by Rat/Human Organic Anion Transporters OAT1 and OAT3

Abstract: Kynurenic acid, a tryptophan metabolite, is involved in psychiatric disease. Our laboratory previously described its transport by rat/human organic anion transporters rOAT1, hOAT1, rOAT3 and hOAT3, which are involved in drug disposition. In this study, we performed an uptake experiment using Xenopus laevis oocytes to examine the transport of xanthurenic acid, a tryptophan catabolite and kynurenic acid analog, by various transporters. All the transporters tested stimulated the uptake of xanthurenic acid into oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…The upregulation of isoatp4056 transcripts in the salivary glands of unfed ticks and in tick cells suggests its important role in the survival and colonization of A. phagocytophilum in tick cells. Studies have shown that human OATs (structurally similar to OATPs) are the transporters for XA 30 . Ticks encode kynurenine aminotransferase (KAT) that could participate in the synthesis of both kynurenate and xanthurenate (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulation of isoatp4056 transcripts in the salivary glands of unfed ticks and in tick cells suggests its important role in the survival and colonization of A. phagocytophilum in tick cells. Studies have shown that human OATs (structurally similar to OATPs) are the transporters for XA 30 . Ticks encode kynurenine aminotransferase (KAT) that could participate in the synthesis of both kynurenate and xanthurenate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Human organic anion and cation transporters are classified into organic anion transporting polypeptides (OATPs), organic anion transporters (OATs) and organic cation transporters (OCTs) 27 . These families of proteins are highly conserved molecules among various vertebrates that play important roles in the influx of several metabolites including xanthurenic acid (XA), a metabolite from the tryptophan oxidation pathway 27 30 . Humans encode 11 OATPs that are localized to barrier epithelial cells 27 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Probably using the same two transporters – one Na + -dependent and one Na + -independent – as kynurenine (Speciale and Schwarcz, 1990), brain cells then actively accumulate 3-HK (Eastman et al, 1992), though the mechanism responsible for the release of newly formed XA has not been elaborated so far. Interestingly, and again in analogy to kynurenic acid (Uwai et al, 2012), XA can be removed from the extracellular space by the organic anion transporters OAT1 and OAT3 (Uwai and Honjo, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In kidney, XA is transported by organic anion transporters 1 (OAT1) and organic anion transporters 3 (OAT3). (22) The function of organic anion transporters (OATs) expressed on the brush border and basolateral membrane of tubular cells of the kidney and belonging to the SLC22A family of drug transporters has now been well-characterized. (23) OAT1 plays a major role, along with OAT3, in the rate-limiting step of excretion of toxins and metabolites from the body into urine.…”
Section: Discussionmentioning
confidence: 99%